DEVELOPMENT OF MAGAZINE ON MADURA SALT THEME WITH ETHNOSCIENCE APPROACH TO IMPROVE STUDENT’S CHARACTER - Hadi, Wiwin Puspita; Muharrami, Laila Khamsatul; Hidayati, Yunin; Rosidi, Irsad; Maryamah, Siti (Unnes Science Education Journal, 2019)
Ethnoscience based teaching material is interest research because it deals with efforts to develop and preserve the values ​​of local wisdom that considered in curriculum development especially in the face of the increasingly rapid industrial revolution era. This type of research is the Research and Development (R & D). The research used the ADDIE development model which consists of analyze, design, development, implementation, evaluation stages. The subjects of this study were students from SMPN 2 Socah Bangkalan. Data analyzed with qualitative and quantitative descriptive. Based on the research, it can be concluded that the results of the average assessment of the feasibility test of the material aspects are 85.79% validity with appropriate categories, reliability 96.22% with very high- reliability categories and the media aspect is 91.76% validity with appropriately used without revisions, reliability of 95.08% with a very high. Integrated science type webbed based on ethnoscience salt theme was declared feasible for use in learning and effectively used for the formation of student’s characters.